Penerapan Pendekatan Open-Ended Learning dalam Pembelajaran Matematika Materi SPLDV Pada Siswa SMP Negeri 1 Modayag Barat - Maudy Amalia Bin Eli; Vivian E. Regar; Oltje T. Sambuaga (Neolectura, 2022)
This study aims to determine student learning outcomes using the Application of the Open-Ended Learning Approach in Mathematics Learning for SPLDV Materials at SMP Negeri 1 Modayag Barat. This study uses a Posttest only control design. The subjects of this study were class VIII C as the Experiment class which consisted of 23 students and class VIII A as the Control class which consisted of 20 students at SMP Negeri 1 Modayag Barat. The data obtained are the results of the posttest in the experimental class and control class. With the average learning outcomes of the Experiment class 87.4 and the average learning outcomes of the Control class 82.75. The normality test of the data was met with the data being normally distributed. The results of data analysis with a significance level of 0.05 obtained t_count=1.9220174521>t_table=1.68288. Based on the results of this study, student learning outcomes using the Open-Ended Learning approach in learning a linear equation system of two variables are higher than student learning outcomes using conventional learning.